PENGARUH PERSEDIAAN BARANG DAGANG TERHADAP LABA USAHA PADA PT. GRAHA LAYAR PRIMA (CGV BLITZ) BANDUNG - Euis Hernawati (POLITEKNIK PIKSI GANESHA, 2021)
This research was aimed to know the influence merchandise inventory to operating income at PT Graha Layar Prima (CGV Blitz). The method used in this research was quantitive analysis with taking samples for period January-December 2018. Data collection used interview observations and completed by literature study which related to the subject. The analysis techniques used is the pearson product moment correlation analysis, coefficient determination, linear regression and test hypothesis. Based on the results of calculations with the use of statistical applications, the results obtained from the correlation coefficient of 0.621 shows the relationship of operating income and merchandise inventory included in the strong category. While the influence of the merchandise inventory against operating income of 38.56% and the rest is influenced by other factors not examined.